Genotoxicity of hormonal steroids - Joosten, H.F.P; van Acker, F.A.A; van den Dobbelsteen, D.J; Horbach, G.J.M.J; Krajnc, E.I (Toxicology letters, 2004)
Hormonal steroids have a widespread use in medicine and their side effects are continuously debated. The possible genotoxic activity of steroids has been the subject of many investigations. The natural estrogens estradiol, estrone and estriol are generally negative in the ICH core battery of tests, but several positive results have been obtained when using additional endpoints of genotoxicity. The genotoxic activity of the 4-hydroxy metabolites of estradiol and estrone is well established. The synthetic steroidal estrogens have a comparable profile of negative and positive test results. Cyproterone acetate and some of its analogues have a special position within the group of progestins. Their genotoxic potential has been established. Other progestins are generally negative in the routine tests. Anti-glucocorticoids, anti-progestins, corticosteroids, androgens, anabolics and anti-androgens appear to be devoid of genotoxic activities. The genotoxic potential of estradiol, estrone and cyproterone acetate with its analogues may play no role under normal physiological and therapeutic conditions. The metabolic conditions that are needed for the formation of DNA-reactive metabolites and oxygen radicals may not be present in humans. Epidemiological cancer data seem to support this view. The importance of thresholds in the dose–effect-relationship of genotoxicity data and their use in risk assessment is discussed.